The Effectiveness of Poster Media on Senior High School Students' Communication Skills on Plant Tissue Concept - Alya, Mutiara; Cahyani, Alifia; Erni, Erni; Mahrawi, Mahrawi (Jurnal Pendidikan Indonesia Gemilang, 2023)
One of the human needs is communication; communication is an activity of exchanging information verbally and non-verbally with one another to change behavior (Yanti, 2019). Learning media needed that can be used as a communication tool or intermediary that the sender will convey with the aim that the recipient can more easily receive the information conveyed (Megawati, 2017). One of the learning media used in the learning process is a poster. Poster learning media is said to be good if it includes legibility, visibility, readability, and composition (Pauwels, 2015). In biology learning, poster media is often used. One of the biological materials that use poster media is plant tissue material. Plant tissue materials study plant tissue facts from various cutting techniques and are poured into images so that studying these materials relies on pictures of plant tissue incisions (Pratama et al., 2022). The results of this study have better changes and have a role in changing the verbal and non-verbal communication of students. This poster model is effective for use on plant tissue materials, where the pictures on the poster can make it easier to understand the material. At least it consists of research objectives, methods, results and interpretations, conclusions.